Meningkatkan Keterampilan Sablon Totebag Melalui Analisis Tugas Bagi Anak Tunarungu - Febriyandi, Febriyandi; Z, Martias (Jurnal Penelitian Pendidikan Khusus, 2022)
This study aims to prove whether task analysis can improve children's ability to improve totebag screen printing skills for deaf children. This research uses classroom action research with the implementation of two cycles. By using task analysis, a complex way of working is made into more specific steps organized into simple and easy-to-understand steps. Based on the results of the study, children's ability to make tote bag screen printing increased compared to before using task analysis. It is evident from the results of research using task analysis can improve the ability to make totebag screen printing.